Phylogenetic analyses and in-seedling expression of ammonium and nitrate transporters in wheat - Prabin Bajgain (Nature Portfolio, 2018)
Abstract Plants deploy several ammonium transporter (AMT) and nitrate transporter (NRT) genes to acquire NH4 + and NO3 − from the soil into the roots and then transport them to other plant organs. Coding sequences of wheat genes obtained from ENSEMBL were aligned to known AMT and NRT sequences of Arabidopsis, barley, maize, rice, and wheat to retrieve homologous genes. Bayesian phylogenetic relationships among these genes showed distinct classification of sequences with significant homology to NRT1, NRT2, and NRT3 (NAR2). Inter-species gene duplication analysis showed that eight AMT and 77 NRT genes were orthologous to the AMT and NRT genes of aforementioned plant species. Expression patterns of these genes were studied via whole transcriptome sequencing of 21-day old seedlings of five spring wheat lines. Eight AMT and 52 NRT genes were differentially expressed between root and shoot; and 131 genes did not express neither in root nor in shoot of 21-day old seedlings. Homeologous genes in the A, B, and D genomes, characterized by high sequence homology, revealed that their counterparts exhibited different expression patterns. This complement and evolutionary relationship of wheat AMT and NRT genes is expected to help in development of wheat germplasm with increased efficiency in nitrogen uptake and usage.